Deteksi Dini Perkembangan Anak Usia 4-6 tahun di TK RA AMDADIYAH Doko Kecamatan Ngasem Kediri dengan Metode PEDS - Novita Setyowati; Erfan Arif Romadhon (coba, 2013)
In early age which in usually a golden age and a criticak period child, it is required to do an early detection proposed whether there is development disorder there. The purpose of this study to determine early detection for the growth of child in 4-6 years old in TK RA AMDADIYAH Doko sub distrrict Ngasem Kediri with using PEDS methode. Design method in this research is description with using quota sampling and the population 67 people. The sample of which 40 respondents. The variabel is a early detection for the growth of child in 4-6 years old in TK RA AMDADIYAH Doko Kecamatan Ngasem Kediri with using PEDS method. The result of this study to disturb growth for resptif language (15%) , Behavior (10%) don’t to disturb (10%) , government (7,5%) , delicate motorik (5%), couse motorik (5%) , ekspresif language (5%). The included of this study the child in criticac disturb for growth aspect can because exterion factor : prenatal factor , brought factor , braith prenatal , factor this study date for drawing 4.4 of most (65%) responded can’t information to do early detection for the child because growth child concluded for parent jaster. Key word : Early detection for the growth , Growth , PEDS